The Impact of Spin-Off Policy To The Profitability On Indonesian Islamic Banking Industry - Abdul Hamid (Faculty of Shariah and Law, UIN Syarif Hidayatullah Jakarta, 2015)
The purpose of this paper is to analyze that the spinoff policy that based on Islamic Banking Act No. 21/2008 had an impact on the profitability ratio of Islamic banking industry in Indonesia. This research used ordinary least square regression. The variable used in this paper is spin-off which is used as a dummy variable, and also included the internal factor of industry such as deposit margin, non-performing financing (NPF), and efficiency ratio (measured by BOPO). The result showed that dummy variable of spin-off, NPF and BOPO had an impact on the profitability in Indonesian Islamic banking industry. The implication of this result is spin-off policy had a good impact on the profitability in Indonesian Islamic banking industry. According to this result, Bank Indonesia should stimulate the Islamic banking unit to spin-off from their parents conventional banks.DOI:10.15408/aiq.v7i1.1363